For What Purpose? The Australian Government and the Use of Creative Commons Licences - Dilan Thampapillai (Bond Law Review)
The Australian Government has overwhelmingly adopted the use of Creative Commons licences to facilitate the dissemination of public sector information. However, very little is understood about the consequences in law and policy of using CC licences online on a mass scale. This article considers whether the Australian Government’s use of CC licences goes beyond a mere permission to use and tends towards contract. The Government might intend that the CC licences be no more than a conditional promise, but the obsequious nature of contract law makes it quite possible that a browsewrap agreement exists in this context. Further, this article considers how the Australian Government is actually using CC licences and questions whether the endeavour is ultimately worthwhile.